2016
DOI: 10.1590/0104-07072016004460015
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework for the Study of Moral Distress in Nurses

Abstract: The objective of this reflective study was to propose conceptual elements for the analysis of moral distress as a process that articulates various concepts of moral experience. The moral distress is explored as a phenomenon manifested in different scenarios and dimensions of labor - care, management and education. Although a relative consensus exists on the concept and comparable empirical results in several countries, there are limited studies that explore theoretical gaps, critical points and possibilities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(86 citation statements)
references
References 26 publications
0
66
0
20
Order By: Relevance
“…These sources have been shown to reflect various ‘internal’ and ‘external’ causes (Woods et al ). Whilst these distinctions may seem vague, it is often thought that the internal causes of moral distress involve psychological uneasiness related to an individual’s moral perceptions and subsequent actions as a professional nurse; and the external causes are often found to involve morally disturbing factors that are associated with the ‘ethical climate’ of a unit or ward that is often difficult for nurses to control (Ramos et al ). As a result, and whether internally or externally generated, or both, moral distress may occur.…”
Section: Introductionmentioning
confidence: 99%
“…These sources have been shown to reflect various ‘internal’ and ‘external’ causes (Woods et al ). Whilst these distinctions may seem vague, it is often thought that the internal causes of moral distress involve psychological uneasiness related to an individual’s moral perceptions and subsequent actions as a professional nurse; and the external causes are often found to involve morally disturbing factors that are associated with the ‘ethical climate’ of a unit or ward that is often difficult for nurses to control (Ramos et al ). As a result, and whether internally or externally generated, or both, moral distress may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is deemed important to support and stimulate strategies that enhance this competence to improve professionals' sensitivity to ethical problems of their daily work. (1,26) The study had as limitations low participation, and participants' difficulty to express themselves on such a complex issue, which justifies further studies. It is suggested that this result may be associated with insecurity, institutional political issues, and even the feeling of disbelief in the return that an academic study can bring to professional practice, especially when the reported causes refer to issues affecting nursing activities in various contexts, and not just for the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Identified as practical wisdom, this sensitivity is a critical and reflective analysis of oneself, one's actions, thinking and being. (1,12) Some discrepancies found in the data collected from the two groups are not surprising, as it is a national level study and a diversity of problems and labor situations among the different realities is expected. A regionalized analysis of the data could reveal interesting differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The importance of discussing the scope and limits of the construct and the researches performed until now is highlighted. [16][17] The Corley 18 -Moral Distress Scale -is a pioneer in MD studies, resulting in applications and adaptations for different health facilities. Its translation and validation, and subsequent adaptation, were performed in Brazil in 2012 and 2014.…”
Section: Introductionmentioning
confidence: 99%